(untitled) (Texas Journal of Medical Science, 2024)
This study uses annual time series data of HIV Prevalence among individuals aged 15-49 years for Belarus from 1990 to 2020 to predict future trends of HIV prevalence over the period 2021 to 2030. The study utilizes Holt’s double exponential smoothing model. The optimal values of smoothing constants α and β are 0.8 and 0.1 respectively based on minimum MSE. The results of the study indicate that annual HIV prevalence among individuals aged 15-49 years will continue on an upward trend over the out of sample period. Therefore, we encourage authorities to strengthen HIV prevention strategies which include behavior change interventions, correct and consistent use of condoms, pre-exposure prophylaxis for high risk groups, post exposure prophylaxis and voluntary medical circumcision among other WHO recommended strategies.